2009
DOI: 10.1007/s11904-009-0011-2
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral medications during pregnancy for therapy or prophylaxis

Abstract: The use of combination antiretroviral therapy during pregnancy has enabled us to decrease perinatal HIV transmission to less than 1%, in areas with adequate resources. Questions remain regarding the safety of these medications for the mother, fetus, and child. Recent publications present conflicting data about associations between antiretrovirals and prematurity and other adverse pregnancy outcomes, and if highly active antiretroviral therapy (HAART) is necessary for all pregnant women. The pharmacokinetics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…45 Additionally, prophylactic use of antiretroviral therapy during pregnancy and in the newborn has decreased mother-to-child-transmission to less than 1%. 46,47 Although it is possible that participants interpreted this item as referring to pregnant mothers not treated with antiretroviral therapy and ignored the difference between HIV and AIDS, the misconception that mother-to-child-transmission is unavoidable may decrease motivation for prenatal HIV testing among young pregnant African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…45 Additionally, prophylactic use of antiretroviral therapy during pregnancy and in the newborn has decreased mother-to-child-transmission to less than 1%. 46,47 Although it is possible that participants interpreted this item as referring to pregnant mothers not treated with antiretroviral therapy and ignored the difference between HIV and AIDS, the misconception that mother-to-child-transmission is unavoidable may decrease motivation for prenatal HIV testing among young pregnant African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious complications of IDU include but are not limited to HIV, hepatitis B, and hepatitis C 43–45 . While the negative consequences of IDU are not unique to pregnant women, special consideration must be paid to pregnant women with HIV in order to prevent perinatal transmission 46 . This is further complicated for women in rural areas where access to specialized HIV care may be limited 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Factors specific to pregnancy may include increased medication intolerance (especially gastrointestinal), increased medication side effects (anemia’s or other), or altered pharmacokinetics. 20, 21, 22 Several studies have reported lower area under the plasma concentration time curve (AUC) in the third trimester with both lopinavir/ritonavir 23,24 and nelfinavir, 24 but the association between lower drug levels during pregnancy and virologic outcome at delivery has not been studied. Many experts, however, consider it to be reasonable to increase the dose of certain PI’s during the third trimester when viral load remains unsuppressed in the setting of good medication adherence.…”
Section: Discussionmentioning
confidence: 99%